Rumen morphometrics of Nellore cattle submitted to either nutritional restriction or intake of concentrate feedstuffs prior to adaptation period. - Reis, B. Q. [UNESP] (2017)
Sao Paulo State Univ UNESP, Dracena Campus, Dracena, Brazil